Clonidine as adjuvant to 0.375% ropivacaine for ultrasonography-guided anterior femoral sciatic nerve block in lower limb surgery: A single-blind, randomized trial - Yohanes Suandrianno; Putu Kurniyanta; Tjokorda Gede Agung Senapathi; Made Widnyana (Bali Journal of Anesthesiology, 2024)
Background: Clonidine as an adjuvant has been known to increase the duration of nerve block and postoperative analgesia and reduce inflammatory responses. This study was conducted to determine the comparison between subjects undergoing lower limb surgery with the sciatic and femoral nerve block anesthesia technique using clonidine as an adjuvant and those without. Materials and Methods: This study was a single-blind, randomized clinical trial on subjects who underwent lower limb surgery. Subjects were divided into two groups with 25 subjects each. Group A received a combination of anterior femoral sciatic nerve block anesthesia using 0.375% ropivacaine and clonidine 0.5 µg/kg, whereas group B received only 0.375% ropivacaine. Outcome variables included hemodynamic stability, first-dose patient-controlled analgesia (PCA) requirement, analgesic consumption, and platelet-to-lymphocyte ratio (PLR) changes. Results: The groups were comparable in terms of age, gender, mean arterial pressure, and heart rate. The time to first PCA requirement was higher in group A (12.44 ± 0.84 h vs. 8.48 ± 0.69 h, P < 0.001). Furthermore, the total postoperative opioid requirement within the first 24 h was lower in group A (11.96 ± 1.51 vs. 20.64 ± 3.67, P < 0.001). Meanwhile, the mean difference between preoperative and postoperative for PLR was also favored in group A (25.84 ± 17.91% vs. 64.02 ± 40.4%, P = 0.004, respectively). Conclusions: The addition of 0.5 µg/kg clonidine to anterior femoral sciatic nerve block in patients undergoing lower limb surgery extended the time to the first PCA dose requirement, reduced total morphine consumption within 24 h postoperative, and reduced PLR changes.